Indurated plaques on the scalp of a 14-year old female. - Guareschi, E.; Ricci, C.; Cavazza, A.; Di Lernia, V. (European Journal of Pediatric Dermatology, 2007)
Precursor B-cell lymphoblastic lymphoma (pre B-cell LYL) is a rare high-grade neo- plasm which affects mostly young people. It occurs most frequently in females involving usually extranodal sites, most often the skin or bone. Cutaneous lesions are commonly located on the head and neck. The Authors present a 14-year-old girl who referred for the presence of erythematous plaques of the forehead and the scalp. Histological examination of the biopsy specimen showed diffuse cutaneous infiltration of precursor B-cells. Immunohistochemistry revealed B phenotype TdT+; CD79a+; CD10+. A diagnosis of acute pre B leukemia/lymphoma was made. An allogeneic stem cell transplantation from HLA-compatible donor was performed with clinical and laboratoristic remission of the hematological disease for 12 months.